Prospective study to evaluate management of ectopic pregnancy in a tertiary care centre - ., Bhavna; Pathania, Kushla; Gupta, Kumud Bala; Kaushal, Sushruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: To study the pattern of management of ectopic pregnancy in a referral Centre in North India. Methods: This prospective study was conducted over a period of one year in the department of obstetrics and gynecology, in a tertiary care Centre in North India. Total number of cases who reported to hospital with ectopic pregnancy during the study period were 110. All the cases were analyzed and managed either with conservative, medical or surgical treatment depending on the condition of cases at the time of presentation to the hospital. Frequencies of different variables were compared by chi square test using Graphpad Prism 9, p value less than 0.05 was considered statistically significant. Results: The incidence of ectopic pregnancies reported in present study was 18.62 per 1,000 deliveries. Total of 110 cases with ectopic pregnancy reported to hospital during the study period. Mean age of the cases was 28.72 years. Out of 110 cases, laparotomy was performed in 100 cases and medical management in 10 cases. Medical management failed in one case and necessitated surgery in that case. There was no maternal mortality during the study period. Conclusion: Most of the cases presented late to the hospital due to lack of awareness, topographically tough terrain in Himachal with limited transport facilities which delayed management of ectopic pregnancy and precludes conservative management either in the form of medical management or conservative surgery. Screening of high-risk cases, early diagnosis, early referral and early intervention reduces the maternal mortality and morbidity. So awareness at the primary health care level is the necessity of the hour.